Chronic stress induces meiotic arrest failure and ovarian reserve decline via the cAMP signaling pathway - Jiang, Yiwen; Xu, Jing; Tao, Chengqiu; Lin, Yunying; Lin, Xiaoqi; Li, Ke; Liu, Qiyu; Saiyin, Hexige; Hu, Shuanggang; Yao, Guangxin; Sun, Yun; Zhang, Feng; et al. (Frontiers in Endocrinology, 2023)
Chronic stress is suspected to be a causal factor of female subfertility; however, the underlying mechanisms remain unclear. Here, we found that chronic stress inhibited the cyclic adenosine 3′,5′-monophosphate (cAMP) signaling pathway, leading to ovarian reserve decline in mice. A chronic stress model was constructed using restraint stress for 8 weeks. An elongated estrous cycle and a significant increase in the number of atretic follicles were observed in the stress group. We identified a significant increase in meiotic arrest failure (MAF) in oocytes in the stress group, characterized by condensed metaphase chromosomes, assembled spindles, or polar bodies in the oocytes. Whole-mount ovarian reserve estimation at the single-oocyte level using the CUBIC method (clear, unobstructed brain/body imaging cocktails and computational analysis) revealed a significant decrease in quiescent oocytes from 2,261/ovary in the control group to 1,373/ovary in the stress group. The number of growing oocytes also significantly decreased from 220/ovary in the control group to 150/ovary in the stress group. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis of the meiotic arrest maintenance pathways revealed significant downregulation of Gpr3, Nppc, and Npr2 in the stress group. These results indicate that blocking cAMP production contributes to MAF and a decline in ovarian reserve. Overall, we present new insights into the mechanisms underlying chronic-stress-induced oocyte loss and potential targets for ovarian reserve preservation.